HAKIKAT DAN DASAR TEOLOGIS PENDIDIKAN AGAMA KRISTEN - Icha Christian Silalahi; Rahmat Simbolon; Edelwis Pardosi; Yemima Meidiana Rista Br. Sembiring; Baginda Sitompul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Christian Religious Education is an integral part of believers' lives that functions to shape faith, character, and spirituality based on God's Word. In its implementation, CRE requires a strong theological foundation in order to fulfill its role as a means of holistic human development. This article aims to examine the nature and theological foundations of Christian Religious Education, including the concept of theology in Christian education, the nature of education from a Christian perspective, the biblical foundations of Christian Religious Education in the Old and New Testaments, the Great Commission as the basis of Christian education, the purpose of education according to God's will, and the relationship between theology and education. This study employs a qualitative method with a library research approach through the examination of books, scholarly articles, and other relevant academic sources. The data were analyzed using content analysis techniques to obtain a systematic understanding of the concepts under study. The findings indicate that Christian Religious Education is rooted in biblical theology that recognizes God as the source and ultimate goal of education. Its primary foundations are found in God's command to teach His Word and in Jesus Christ's Great Commission to make disciples of all nations. Christian education aims to form individuals who know God, possess Christlike character, develop their potential holistically, and become witnesses of Christ in society. Therefore, the integration of theology and education serves as an essential foundation for developing relevant and transformative Christian education.